Quantitative measures of respect and social inclusion in children: overview and recommendations - Tredoux , Colin G.; Mohd. Noor, Noraini; de Paulo, Lisa (Taylor & Francis, 2009)
An important task in empirical research on prejudice, respect and inclusion in children is the measurement of attitudes and behaviours. Although the literature on measuring attitudes and behaviour in adults is of some assistance, it is also clear that the task of measuring children’s attitudes and behaviour presents particular problems and challenges. We provide an overview in this paper of a number of currently used measures. Their strengths and limitations are outlined, and recommendations are made for contemporary practice. This review has been undertaken by the Una Quantitative Methods Learning Group. Una is a global learning initiative on children and ethnic diversity (see: www.unaglobal.org).